Evaluation of special endurance exercises according to the Cosmin test for maximum oxygen consumption and its relation to (1500) meters Running achievement - Amanh, Mohammed (Journal of Physical Education, 2018)
Evaluation of special endurance exercises according to the Cosmin test for maximum oxygen consumption and its relation to (1500) meters Running achievement The importance of the research lies in maximum oxygen uptake Vo2max in 1500m running event as well as paying attention to special physical traits of the event. The researcher used the descriptive method. The subjects were (5) advance runners who represent the Iraqi league in 1500m running. The data was collected and treated using proper statistical operations to conclude that endurance training according to Cosmin test needs to be reconsidered when conducted on 1500 m running. In addition to that the researcher concluded that 1500m runners should maintain Vo2max as an indicator for improvement. Finally the researcher recommended using follow up procedures to evaluate endurance training for each runner in 1500m event.